CLIMATE ASSESSMENT OF KHEMCHIK–KURTUSHIBINSKY FOREST DISTRICT THE REPUBLIC OF TYVA (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
The paper presents an analysis of changes in climatic parameters (air temperature, relative air humidity, evaporation, precipitation and wind speed projection) in the Khemchik–Kurtushibinsky district of mountain steppes, mountain-taiga grass larch forests of the Republic of Tyva. The insufficient number of meteorological stations and the lack of data on altitude levels motivated the use of ERA-5 reanalysis data. The assessment was carried out on the basis of data for the period 1961–2020 in the altitude range from 500 to 2200 m and more a.s.l. Trends in changes in the main climatic data were identified, the rates of their changes were calculated, and anomalies were assessed. The results show significant changes in climatic parameters, especially at altitudes of 500–1000 m a.s.l., which may be associated with global climate change.
Keywords: mountain region; forest-growing district; climate change trends